AL BARAKA BANKING GROUP - Nizomova Mehrangiz Jamoliddinzoda (American Journals, 2022)
In this article, the brief history, branches and financial results of the international Al Baraka Banking Group, which ranks high on all sides, are discussed in detail, and conclusions are given on the application of its experience in Uzbekistan.
Keywords: ABG, Islamic banking, e-banking, Covid-19.